Developmental Cycle and Genome Analysis of Protochlamydia massiliensis sp. nov. a New Species in the Parachlamydiacae Family - Benamar, Samia; Bou Khalil, Jacques Y.; Blanc-Tailleur, Caroline; Bilen, Melhem; Barrassi, Lina; La Scola, Bernard (Frontiers in Cellular and Infection Microbiology, 2017)
Amoeba-associated microorganisms (AAMs) are frequently isolated from water networks. In this paper, we report the isolation and characterization of Protochlamydia massiliensis, an obligate intracellular Gram-negative bacterium belonging to the Parachlamydiaceae family in the Chlamydiales order, from a cooling water tower. This bacterium was isolated on Vermamoeba vermiformis. It has a multiple range of hosts among amoeba and is characterized by a typical replication cycle of Chlamydiae with a particularity, recently shown in some chlamydia, which is the absence of inclusion vacuoles in the Vermamoeba vermiformis host, adding by this a new member of Chlamydiae undergoing developmental cycle changes in the newly adapted host V. vermiformis. Draft genome sequencing revealed a chromosome of 2,86 Mb consisting of four contigs and a plasmid of 92 Kb.